2009
DOI: 10.1098/rsta.2009.0112
|View full text |Cite
|
Sign up to set email alerts
|

Aberration-corrected scanning transmission electron microscopy: from atomic imaging and analysis to solving energy problems

Abstract: The new possibilities of aberration-corrected scanning transmission electron microscopy (STEM) extend far beyond the factor of 2 or more in lateral resolution that was the original motivation. The smaller probe also gives enhanced single atom sensitivity, both for imaging and for spectroscopy, enabling light elements to be detected in a Z-contrast image and giving much improved phase contrast imaging using the bright field detector with pixel-by-pixel correlation with the Z-contrast image. Furthermore, the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 74 publications
(103 reference statements)
0
58
0
Order By: Relevance
“…Although the X-ray energy-dispersive spectroscopy (XEDS) technique for STEM already presented the possibility of atomic resolution spectroscopy by using an optimized experimental setup, [36] the combined use of high brightness electron guns, Cs-corrected STEM microscopes, [8] enhanced X-ray detectors, [37] and the application of statistical methods on data treatment [15,38] have recently increased the possibilities of atomic resolution characterization. [39,40] In addition to the above-mentioned collection angle optimization, these enhancements are mainly related to two other features that determine the efficiency of XEDS analysis.…”
Section: Xedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the X-ray energy-dispersive spectroscopy (XEDS) technique for STEM already presented the possibility of atomic resolution spectroscopy by using an optimized experimental setup, [36] the combined use of high brightness electron guns, Cs-corrected STEM microscopes, [8] enhanced X-ray detectors, [37] and the application of statistical methods on data treatment [15,38] have recently increased the possibilities of atomic resolution characterization. [39,40] In addition to the above-mentioned collection angle optimization, these enhancements are mainly related to two other features that determine the efficiency of XEDS analysis.…”
Section: Xedsmentioning
confidence: 99%
“…Although STEM is approximately as old as TEM and SEM techniques, [6] some recent instrumental developments have greatly enhanced its performance and supported a reasonable number of breakthrough results. Among these advances are the spherical aberration (Cs) and chromatic aberration (Cc) corrections, [7][8][9] monochromator implementation, [9] and improved synchronous systems for data acquisition. [10] In addition to instrumental enhancements, several theoretical tools were developed and implemented to improve the characterization possibilities and to provide more reliable quantitative analysis, among them are more accurate image simulation and spectrum analysis procedures, [11,12] the implementation of deconvolution models, [13,14] and multivariate statistical analysis (MSA) [15] for improved information extraction from raw data.…”
Section: Introductionmentioning
confidence: 99%
“…Pennycook et al (2009) demonstrated the power of aberration-corrected scanning transmission electron microscopy (STEM) for solving materials problems at the atomic level of resolution, while Urban et al (2009) described the value of being able to tune spherical aberration to optimize the information available from aberration-corrected transmission electron microscopy (TEM). Improving resolution and quantification by the combination of a set of images taken at different focus and illumination tilt settings in an aberration-corrected environment was the theme of the contribution presented by Kirkland (Haigh et al 2009).…”
Section: New Possibilities With Aberration-corrected Electron Microscopymentioning
confidence: 99%
“…[7][8][9] The clear view of atom positions enables direct comparison of experiment with theory modeling. 7,8,[10][11][12] In this work, we employ the contrast based on the high-angle scattering of electrons (Z-contrast) in a STEM mode to image the cation sub-lattice only, which allows for directly measuring vacancy-induced displacements of cations in YSZ. In conjunction with density-functional theory (DFT) calculations, we show that the location and concentration of oxygen vacancies in YSZ can be determined from the measured atomic displacements of the cation sub-lattice.…”
Section: Introductionmentioning
confidence: 99%